Diagnostic value and Clinical Significance of serum Proteins Ki-67, PI3K, and Fascin in Patients with Oral Squamous Cell Carcinoma: Clinical Significance of serum Proteins Ki-67, PI3K, and Fascin - Guanglian, Yang (Journal of Medical Biochemistry, 2025)
Objective: This study was designed to explore the expression and significance of KI-67, phosphoinositide-3-kinase (PI3K), and Fascin in oral squamous cell carcinoma (OSCC). Methods: Thirty-five patients with OSCC admitted to our hospital from January 2019 to December 2020 were included. Tumor tissue and paracancerous tissue samples of all patients were collected. Immunohistochemical staining was performed to determine the expression of Ki-67, PI3K, and Fascin. Pearson correlation analysis was employed to analyze the association of clinicopathological characteristics with Ki-67, PI3K, fascia, and oral cancer. SPSS 23.0 was used for data analysis. Results: Significantly higher positive expression rates of Ki-67, PI3K, and Fascin were detected in OSCC tissues, well-differentiated OSCC tissues, and OSCC tissues with lymph node metastasis and cancer cells infiltrating to peripheral muscle, vs paracancerous tissues, moderately and poorly differentiated OSCC tissues, and OSCC tissues without lymph node metastasis, respectively (all P0.05). Ki-67 was positively correlated with PI3K (r=0.930, P=0.019) and Fascin (r=0.928, P=0.019), and Fascin was positively correlated with PI3K (r=0.991, P=0.001). Conclusion: The relative expression levels of Ki-67, PI3K, and Fascin are related to lymph node metastasis, perifocal muscle invasion, and pathological staging of patients with OSCC, which indicates their potential involvement in the occurrence and progression of OSCC.
Keywords: oral squamous cell carcinoma; Ki-67; phosphoinositide-3-kinase; Fascin